The Role of Profitability in Mediating the Effect of Firm Growth on Debt Policy - Ahmad, Yusril Maulana; Karnowahadi, Karnowahadi -; Rini, Nur - (Politeknik Negeri Semarang, 2021)
This study aims to analyze the effect of Firm Growth on Debt Policy with ProfitabiliSty as mediating variable on infrastructure sector companies listed in the Indonesia Stock Exchange (IDX) for 2016-2020 period. Research population was all infrastructure sector companies listed in the Indonesia Stock Exchange (IDX) of 57 companies, while the research samples were 36 (thirty six) companies selected using purposive sampling technique. The analysis model used in this research was multiple linear regression analysis model and analysis technique used were partial test (t test) and sobel test to test the mediating variable by SPSS 25.00 program. The result of this study showed that the Firm Growth had a negative and significant effect on profitability. Profitability had a negative and significant effect on Debt Policy. Meanwhile, Firm Growth didn’t directly effect on Debt Policy. The mediating role of Profitability as an mediating variable had significantly contributed to the effect of Firm Growth on Debt Policy